Answer:
Step-by-step explanation:
The description is too ambiguous to reconstruct the diagram. You need to post the actual diagram.
That diagram is just one way to view division by a fraction. An easier way: DIVIDING by a fraction is the same as MULTIPLYING by the upside-down fraction. For example,
(1/2) ÷ (1/4) = (1/2) × (4/1) = 2
That doesn’t help you answer this particular question, though.
Answer:
B = A/5h - b; You could use
B = (A - 5hb)/5h This just puts everything over a common denominator.
Step-by-step explanation:
A = 5h (B + b) Divide both sides by 5h
A/5h = B + b Subtract b from both sides.
A/5h - b = B
Answer:
Step-by-step explanation:
I knew the answer sir 112 but hmmm I'm only 7 g
Complete question:
y = 2x² + 2x - 3
x = -2 -1 0 1 2
Answer:
<u>Complete table of values</u>
x: -2 -1 0 1 2
y: 1 -3 -3 1 9
Step-by-step explanation:
Given;
y = 2x² + 2x - 3
To complete the table of values of the equation above, we substitute the value of x into the given equation and solve for y.
when, x = -2
y = 2(-2)² + 2(-2) - 3
y = 8 - 4 - 3
y = 1
when x = -1
y = 2(-1)² + 2(-1) - 3
y = 2 - 2 - 3
y = -3
when x = 0
y = 2(0)² + 2(0) - 3
y = 0 - 0 - 3
y = -3
when x = 1
y = 2(1)² + 2(1) - 3
y = 2 + 2 - 3
y = 1
when x = 2
y = 2(2)² + 2(2) - 3
y = 8 + 4 - 3
y = 9
<u>Complete table</u>
x: -2 -1 0 1 2
y: 1 -3 -3 1 9